Flipbook development based on problem based learning on chemical bonding material - Hamidah Hamidah; Mauliza Mauliza; Jofrishal Jofrishal (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2025)
The Merdeka Curriculum requires interactive digital media, but chemistry learning, especially on chemical bonding material, is still dominated by limited and uninteresting media. Previous studies have produced useful teaching materials, but they are generally small in scale, not yet integrated with PBL, or have not maximized the features of digital flipbooks, so there is still a need for more innovative media. This study developed a flipbook medium based on Problem-Based Learning (PBL) to enhance the effectiveness of chemical bonding instruction. The purpose of this research was to determine the needs, feasibility, practicality, and attractiveness of the developed flipbook. This research employed a Research and Development (R&D) design using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The instruments used consisted of interview questionnaires, needs analysis questionnaires, expert validation questionnaires (media and material), as well as practicality and attractiveness questionnaires. The research subjects were chemistry teachers and high school students at public senior high schools in Langsa City. The results of the teacher needs assessment showed a percentage of 71.1%, categorized as “needed.” Media and material expert validations yielded average scores of 0.87 and 0.83, respectively, both classified as “highly feasible.” The media trials with teachers and students resulted in practicality and attractiveness scores of 95% and 83.09%, respectively, categorized as “highly practical” and “highly attractive.” It can be concluded that the PBL-based flipbook developed in this study is practical, useful, and engaging in supporting more effective learning processes. Therefore, this medium can support the implementation of the Merdeka Curriculum through interactive digital learning. Keywords: flipbook; problem-based learning; chemical bonding. Abstrak. Kurikulum Merdeka menuntut media digital yang interaktif, tetapi pembelajaran kimia, terutama pada materi ikatan kimia masih didominasi media yang terbatas dan kurang menarik. Penelitian sebelumnya menghasilkan bahan ajar yang bermanfaat, namun umumnya berskala kecil, belum terintegrasi PBL, atau belum memaksimalkan fitur flipbook digital, sehingga masih terdapat kebutuhan akan media yang lebih inovatif. Penelitian ini mengembangkan media flipbook berbasis Problem Based Learning (PBL) untuk meningkatkan efektivitas pembelajaran ikatan kimia. Tujuan dari penelitian ini adalah untuk mengetahui kebutuhan, kelayakan, kepraktisan dan kemenarikan media flipbook yang dikembangkan. Jenis penelitian ini merupakan penelitian pengembangan (R&D) yang menggunakan model ADDIE yang meliputi tahap analisis, perancangan, pengembangan, implementasi, dan evaluasi. Instrumen yang digunakan meliputi angket wawancara, angket analisis kebutuhan, angket validasi ahli (media dan materi) serta angket kepraktisan dan kemenarikan. Subjek penelitian ini adalah guru kimia dan siswa SMA Negeri di Kota Langsa. Hasil penilaian kebutuhan guru menunjukkan persentase 71,1% yang diklasifikasikan sebagai “dibutuhkan”. Validasi oleh ahli media dan ahli materi menghasilkan skor rata-rata 0,87 dan 0,83 yang termasuk dalam kategori “sangat layak”. Uji coba media dengan guru dan siswa menghasilkan kepraktisan sebesar 95% dan kemenarikan sebesar 83,09%, yang keduanya termasuk dalam kategori “sangat praktis” dan “sangat menarik”. Dapat disimpulkan bahwa flipbook berbasis PBL yang dikembangkan dinilai praktis, bermanfaat dan menarik untuk mendukung proses pembelajaran yang lebih efektif. Sehingga media ini dapat mendukung implementasi Kurikulum Merdeka berbasis pembelajaran digital interaktif.